The impact of design creativity: Inspirations and timing of stimulation - Guanhua Hou; JingyuChen (Telematics and Informatics Reports, 2023)
Many studies about creativity revealed that design inspiration played an important role in generating innovative ideas, but ignored the influence of stimulation timing on design creativity. To advance such a state, this study used 3(design inspiration: near, middle, and distant domain inspiration)*2(stimulus timing: before idea generation and when idea generation stalls) between group experimental design to investigate the effect of design inspiration and stimulus timing on design creativity. Forty-eight participants were recruited, and divided into six groups to solve a design problem. Design creativity were measured by subjective scales and objective outcomes. The results showed that : (1)near domain inspiration helps designers generate the solution quickly; (2)middle domain inspiration helps designers generate practical solutions; (3)distant domain inspiration helps designers generate the solution with high novelty. The findings of this study provided insights for designers to enhance their design creativity.